Islamic Education Values in Roah Segare Tradition Quranic Studies at Kuranji Dalang Village West Lombok - Ridho, Abdul Rasyid; Nuruddin, Nuruddin (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The tradition of roah segare is known by the people of Kuranji Dalang village as a form of gratitude to Allah SWT for having bestowed natural products on the community through the implementation of the roahsere tradition. On the other hand, this tradition is expected to further strengthen human friendship among humans and to familiarize humans with nature. The implementation of this roah sere tradition in practice indirectly actualizes the educational values of the Qur'an, including the first value of deliberation in Q.s al-syura/42:38, which has implications for the division of work they do, the second is the value of habituation, which has implications for the hereditary tradition, the three exemplary values in Q.s. Al-Ahzab/33:21, which has implications for strengthening good values in this tradition, the four values of brotherhood in Q.s al-Hujurat/49:10, which have implications for cohesiveness and unity in performance, the five values of cooperation and mutual assistance in Q.s. al-Maidah/5:2 which has implications for smoothness and ease in implementing the roah segare tradition, and the six social welfare values in Q.s al-Hasyr/59:9 which has implications for social care among human beings.